A Facile One-pot Synthesis of New Pyrazolopyrimidines and Pyrazolo Pyridines Derivatives - Ahmed, Hatem Abdel Moniem (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A Simple Facile One-pot reaction, novel and efficient rout for the synthesis of substituted pyrazolo [3, 4-d] pyrimidines, and pyrazolo [3, 4-b] pyridines, results from reaction of substituted-5-amino-4-cyanopyrazoles with malononitrile and diethylmalonate respectively. The structures of the products and conceivable mechanisms are discussed. The antibacterial activity of some new synthesized compounds was evaluated and seemed to be significant.